PENGGUNAAN STRATEGI QUESTION STUDENT HAVE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA TEMA INDAHNYAKEBERSAMAAN SUBTEMA KEBERAGAMAN BUDAYA BANGSAKU KELAS IV SEMESTER GANJIL DI SDN 3 ARDIREJO KABUPATEN SITUBONDO TAHUN PELAJARAN 2016/2017 - Erfan Adi Rachman; Nur Holifatuz Zahro (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2017)
The research aims to improve the activity and student learning outcomes by implementing strategies Question Student Have class research subject IV in SDN 3 Ardirejo Situbondo in the academic year 2016/2017. The technique of collecting data through observation, interviews, tests and documentation. Analysis of data using qualitative descriptive analysis. The results of the first cycle of observation activities reached 86.74% active criteria, and observation activity appeared to increase the second cycle to be very active in the amount of 90.53%. The results of the research with the implementation of Question Student Have strategies can improve student learning outcomes in science subjects, in terms of cognitive aspects. While the results of study on the first cycle students' mastery of 86.36%, and the second cycle increased by 90.90%. It is appropriate that the improvement objectives to be achieved investigators. Based on the results of this study concluded that the use of strategies Question Student Have proven to improve learning outcomes Activities and fourth grade students at SDN 3 Ardirejo Situbondo in academic year 2016/2017